Xiaoaiping injection combined with chemotherapy for advanced gastric cancer: An updated systematic review and meta-analysis - Zhou, Xing Qin; Chang, Ya Zhou; Shen, Chao Yan; Han, Jie; Chang, Ren An (Frontiers in Pharmacology, 2022)
Aim: To evaluate the clinical efficacy and safety of Xiaoaiping injection combined with chemotherapy in the treatment of advanced gastric cancer by meta-analysis. Methods: Seven databases, including China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Database, Cochrane Library, PubMed, Embase, and Web of Science, were searched by computer for randomized controlled clinical trials of Xiaoaiping injection combined with chemotherapy in the treatment of gastric cancer. Risk of bias assessment and meta-analysis were performed by Review Manager 5.3 software. Results: There were 16 articles that met the inclusion criteria, with a total of 1236 patients, 617 in the observation group and 619 in the control group. The results of meta-analysis showed that the observation group was better than chemotherapy alone control group in RR [OR=1.86, P<0.00001]; disease control rate (DCR) [OR=2.45, P<0.00001]; Karnofsky performance status (KPS) score [OR=3.21, P<0.00001] or [MD=7.73, P＝0.001]. In terms of biochemical indicators, Xiaoaiping significantly reduced inflammation factors level, including tumor necrosis factor alpha (TNF-α) [MD=-15.00, P<0.00001]; interleukin-6 (IL-6) [MD=-13.00, P<0.00001]; C-reaction protein (CRP) [MD=-5.80, P<0.00001]. Xiaoaiping could enhance immune function, significantly reducing myeloid-derived suppressor cells (MDSCs) [MD=-6.20, P<0.00001] and Treg [MD=-1.70, P<0.00001]. Xiaoaiping injection combined with chemotherapy could significantly decrease tumor markers, including carcinoembryonic antigen (CEA) [MD=-11.64, P<0.00001]; CA199 [MD=-33.57, P=0.02]; CA242 [MD=-20.66, P<0.00001]; CA125 [MD=-12.50, P=0.0005]. In the comparison of adverse reactions, the incidence rate of Xiaoaiping injection group was significantly lower than that of control group. The funnel plot showed that the left and right sides are basically symmetrical, and it can be considered that there is no obvious publication bias. Conclusion: Xiaoaiping injection combined with chemotherapy has better curative effect and less adverse reactions in the treatment of gastric cancer. However, limited by the quality of the included studies, more high-quality studies are still needed to be verified.